Therapeutic Effect of Hypofractionated Stereotactic Radiotherapy Using CyberKnife for High Volume Cavernous Sinus Cavernous Hemangiomas. (17th September 2019) - Huang, Lichao; Sun, Lu; Wang, Weijun; Cui, Zhiqiang; Zhang, Zizhong; Li, Jiwei; Wang, Yao; Wang, Jinyuan; Yu, Xinguang; Ling, Zhipei; Qu, Baolin; Pan, Long Sheng
Objective: To evaluate the efficacy and safety of hypofractionated stereotactic radiotherapy using CyberKnife for high volume cavernous sinus cavernous hemangiomas. Materials and Methods: We collected data from 12 patients with high volume cavernous sinus cavernous hemangiomas treated with hypofractionated stereotactic radiotherapy using CyberKnife in our institute, including 2 men and 10 women/female child, aged 4 to 60 years. Initial tumor volumes ranged from 11.8 to 96.6 cm 3 with a median of 24.3 cm 3 . Irradiation doses were 19.5 Gy with 3 fractions in 2 patients, 21 Gy with 3 fractions in 8 patients, 25 Gy with 5 fractions in 1 patient, and 30 Gy with 3 fractions in 1 patient. We used 109 to 155 beams during treatment, and target volumes reached over 95% of the prescribed dose. Follow-up ranged from 3 to 54 months. We evaluated the efficacy and safety of the CyberKnife system based on changes in the diagnostic images and involved cranial nerves or symptoms. Results: Of the 12 patients, 11 were followed for 3 to 54 months with a mean follow-up of 16.3 months; 1 patient was lost to in-person follow-up. Lesion volumes in the followed 11 patients were calculated after fractionated radiotherapy. All tumor volumes decreased (28.6%-94.1%) and symptoms improved (including blurred vision, visual field defects, diplopia, headaches, and facial numbness) after therapy. Postoperative magnetic resonance images revealed a tumor volume range of 2.8 to 41.0 cm 3 (median, 6.5 cm 3 ), significantly lower compared with the pretreatment range of 11.8 to 70.1 cm 3 (median, 24.3 cm 3 ; T = 0.00, P = .003 < .05). A single patient experienced radiotherapy-related cerebral edema, which resolved after 5 days of mannitol and dexamethasone. Conclusions: Based on the current results, though preliminary, hypofractionated stereotactic radiotherapy using CyberKnife is an effective and safe alternative for high volume cavernous sinus cavernous hemangiomas and is the recommended primary treatment in high-risk patients with this condition.